PELAKSANAAN PERATURAN BUPATI KABUPATEN BENGKALIS NOMOR 15 TAHUN 2010 TENTANG KAWASAN SUAKA PERIKANAN IKAN TERUBUK TAHUN 2011- 2014 - Despri Sandi Wahyu; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Economically and culturally terubuk fish is Idol and the pride of the community District Bengkalis. Seen as the Province of the city "Terubuk". Save the fish terubuk means save the existence of culture and identity as a town of Bengkalis Regency Terubuk. with the publication of the Regulation No. 15 of 2010 Regents about the Asylum Area Fisheries Terubuk Fish intended to safeguard and guarantee the existence, availability, and continuity with the type of fish still maintain and increase the value and diversity of fish resources and the environment in a sustainable way. So the threat of extinction of the fish terubuk in the future could have been avoided. This research aims to find out how the implementation of the Regulation No. 15 of 2010 Regents about the Asylum Area Fisheries Fish Terubuk conducted by the Marine and Fisheries Agency of Bengkalis Regency during the years 2011-2014Type of this research is a descriptive i.e. researchers gives an overview and explanation regarding thephenomenon or social symptoms examined describesvariables that affect the execution of a policy ofsystematically and accurately. Method of data collection is done by means of interviews and the documentationAfter research this is done can be known how the implementation of the Regulation No. 15 of 2010 Regents about the Asylum Area Fisheries Fish Terubuk by the Department of marine and Fisheries begin in 2011-2014. Department of marine and Fisheries already communicate this with some rules of Regent stake holder through the seminars-meetings. The resource that is owned in the form of staff and budget is also already quite well known from the growing number of budget that comes from the regional budget (BUDGETS) for activities related to terubuk fish sanctuary. Supervision became one of the important factors in the success of maintaining fish populations in this terubuk, because there are still many fishermen who do not abide by the rules that already exist and still also do fishing terubuk in the period of peak spawning by reason of economic needs, the Department of marine and Fisheries was not optimally in conducting patrols in the sea as a form of surveillance, it can be known from description of fishermen who very rarely met an employee of the Department of marine and fisheries patrol in the sea. Standard operating procedure (SOP) is a reference in conducting an activity, but so far this has not been the presence of SOP so that the performance of the Department of marine and Fisheries was less the maximum.Environmental pollution in particular became polluted sea water cause decreased and difficult to breed his fish terubuk, water rinse tengker vessel containing remains of fuel oil and also sawdust which is derived from wood factory mill along the river basin (DAS) of Siak eaten by fish terubuk fish easily cause death. Marine and Fisheries Agency acknowledged the existence of the limitation of the Authority (fragmentation) because it's not under the authority of the Department of marine and fisheries.Keywords: Implementation, Local Government, Regional policy